2018
DOI: 10.1590/1678-4685-jbn-3602
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical and laboratory features of urinary tract infections in young infants

Abstract: The male: female ratio for urinary tract infection was 3.3:1. Non-Escherichia coli etiologies should be considered in empirical treatment. Fever was the main symptom. Positive nitrite is highly suggestive of UTI but has low sensitivity; whereas pyuria ≥ 10,000/mL revealed good sensitivity, but low specificity. Peripheral white blood cell count and C-reactive protein concentration have limited usefulness to suggest UTI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
1
2
0
2
Order By: Relevance
“…In our study, pediatric patients with UTI with or without urinary tract malformations had similar clinical symptoms and laboratory measurements. This is consistent with previous studies which showed that the clinical and laboratory features of UTI in children are non-specific ( 8 , 9 , 22 , 23 ). This often contributes to the delayed diagnosis and management of UTI in pediatric patients.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, pediatric patients with UTI with or without urinary tract malformations had similar clinical symptoms and laboratory measurements. This is consistent with previous studies which showed that the clinical and laboratory features of UTI in children are non-specific ( 8 , 9 , 22 , 23 ). This often contributes to the delayed diagnosis and management of UTI in pediatric patients.…”
Section: Discussionsupporting
confidence: 93%
“…It should be noted that prolonged incarceration, associated pathology, or large-scale use of antibiotics and invasive procedures increase the incidence of UTIs. 30 Enterococci are often detected in complicated UTIs, 31 but we have no investigational data available in this study, whether the strains come from an uncomplicated or a complicated UTI.…”
Section: Resultsmentioning
confidence: 85%
“…Uma infecção urinária, por exemplo, que muitas vezes cursa com disúria, pode ser difícil de ser diagnosticada em crianças que não verbalizam. Nesses casos, elas apresentam outros sinais clínicos inespecíficos, como febre, letargia, irritabilidade, vômito, desidratação, anorexia e baixo ganho ponderal; de forma que, na maioria das vezes, a criança terá uma FSSL (LO et al, 2018).…”
Section: Interrogatório Sistematológicounclassified